Common Fixed Point Theorems for Generalized Contractions in Ordered M-Metric Spaces (Contemporary Mathematics, 2025)
This paper seeks to investigate and derive fixed point and common fixed point results for almost generalized contractive mappings and Reich contractions within the framework of partially ordered M-metric spaces. Furthermore, the practical utility and applicability of these findings are demonstrated through illustrative examples. The results presented herein build upon and substantially generalize several foundational studies in the existing literature.
Keywords: partial metric space; M-metric space; fixed point; ordered space; contraction mapping; Reich contraction